2020
DOI: 10.1007/s12328-019-01091-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure associated with diffuse large B-cell lymphoma: an autopsy case report

Abstract: Acute liver failure (ALF) associated with malignant infiltration of the liver is rare and its pathological and radiologic features remain poorly described. An 87-year-old man was admitted to our hospital for anorexia for several days, high-grade fever from the previous day, and liver dysfunction but suddenly died on day 3 of hospitalization due to ventricular fibrillation. The patient was diagnosed at autopsy with malignant diffuse large B-cell lymphoma. To the best of our knowledge, this report represents a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…In those cases, the prognosis has been generally poor, with high rates of in-hospital mortality. Three cases were diagnosed at autopsy [ 11 ]. A summary of previously documented cases of acute liver failure due to infiltration of the liver by non-Hodgkin lymphoma is shown in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those cases, the prognosis has been generally poor, with high rates of in-hospital mortality. Three cases were diagnosed at autopsy [ 11 ]. A summary of previously documented cases of acute liver failure due to infiltration of the liver by non-Hodgkin lymphoma is shown in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Rich et al, liver biopsy was found to be a hallmark in the early diagnosis of such patients [ 4 ], but bone marrow biopsy and gastric biopsy can also help with the diagnosis. Early diagnosis of DLBCL provides the chance for proper treatment of patients with chemotherapy, and this has proved to decrease the mortality rate [ 11 ]. However, liver biopsy should be carefully considered in patients with ALF due to the risk of complications that can be exacerbated by coagulopathy and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver failure (ALF) is a rare but life-threatening condition that causes multiorgan effects [ 1 ]. Although the liver is the most frequent site for metastasis (36%), ALF from malignant infiltration is extremely rare [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver failure (ALF), also known as fulminant hepatic failure, is a clinical phenomenon characterized by severe acute liver injury with encephalopathy and impaired synthetic function (international normalized ratio (INR) >1.5) in a patient without the pre-existing liver disease [ 1 ]. ALF has a variety of causes that include both primary causes as well as secondary ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation